Management of patients with acute lymphoblastic leukemia in routine clinical practice: Minimal residual disease testing, treatment patterns and clinical outcomes in Belgium, Greece and Switzerland. (April 2020) - Deeren, Dries; Balabanov, Stefan; Nickel, Katharina; Giannopoulou, Christina; Gonzalez-McQuire, Sebastian; Kutikova, Lucie; Bouwmeester, Walter; Spyridonidis, Alexandros
Highlights: ALL is associated with considerable clinical and economic burden. Median OS was 28.9 months, 76 % of patients were hospitalized (mean 1.1 time/month). MRD+ patients have worse prognosis than MRD- patients. Median OS for MRD+ patients was 15.3 months; MRD-: not reached. Efforts should be made to adhere to recommendations for MRD testing in clinical guidelines. Abstract: Objectives: To describe real-world management and clinical and economic outcomes of patients with B-cell precursor acute lymphoblastic leukemia (ALL) in Belgium, Greece and Switzerland. Methods: This descriptive, retrospective medical chart review collected patient-level data in 2018 from adults with ≥1 minimal residual disease (MRD) test during front-line ALL treatment. Data were stratified by MRD status. Results: Eighty-two patients were included (median age 44 years, 23 % Philadelphia chromosome-positive; MRD-positive: n = 17, MRD-negative: n = 50, MRD result unknown: n = 15). HyperCVAD (32 %) and HOVON (26 %) were the most frequently used front-line treatment protocols; 22 % of patients received stem cell transplantation. Overall, 76 % of ALL patients were hospitalized (mean 1.1 hospitalization/month). Complete hematological response (CRh) occurred in 66/82 patients (80 %). Median relapse-free survival from CRh was 32.7 months (MRD-positive: 11.7 months; MRD-negative: 33.3 months). Median overall survival from diagnosis was 28.9 months (MRD-positive: 15.3 months; MRD-negative: not reached). Most patients (88 %) were MRD tested during induction; testing rates considerably decreased thereafter (39 % during consolidation). Conclusions: B-cell precursor ALL represents a clinical burden and impacts healthcare resources; MRD-positive patients have worse prognosis than MRD-negative patients. Efforts should be made to adhere to recommendations for MRD testing in clinical guidelines.